Accounting Knowledge, Job Market Considerations, Accounting Students' Career Interest in Public Accounting Field: Financial Rewards as A Moderating Variable - Suyanto Suyanto; Bagas Saputra; Fuadhillah Putri (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This research examines accounting knowledge, job market considerations, and accounting students' career interest in public accounting, with financial rewards as the moderating variable. The primary data was collected using questionnaires spread through Google Forms. The data is measured by using the Likert Scale. The research population consists of Bachelor of Accounting students from throughout Indonesia. Using purposive sampling, this research obtained 91 respondents as the sample. The regression method is used as the data analysis method, and SPSS 23 software is used. The research results indicate that accounting knowledge and job market considerations significantly positively influence accounting students' career interests as public accountants. Financial rewards weaken accounting knowledge on accounting students' career interest in public accounting. Meanwhile, financial rewards strengthen the positive and significant effect of job market considerations on accounting students' career interest in the public accounting field. This research suggests that universities with a prominent role in preparing high-quality accounting graduates are more responsive to changes in the world of work, so it is necessary to improve the quality of the curriculum. In addition, this research is also expected to be a reference for public accounting firms, as financial reward no longer becomes the first consideration for accounting students when choosing a career. Accounting firms must consider other factors when they recruit new employees, such as work-life balance and flexible hours.